2013
DOI: 10.1115/1.4024161
|View full text |Cite
|
Sign up to set email alerts
|

Blood Pressure, Artery Size, and Artery Compliance Parallel Bone Size and Strength in Mice With Differing Ece1 Expression

Abstract: The recombinant congenic mouse strains HcB-8 and HcB-23 differ in femoral shape, size, and strength, with HcB-8 femora being more gracile, more cylindrical, weaker, and having higher Young's modulus. In previous work, we mapped a robust, pleiotropic quantitative trait locus for these bone traits. Ece1, encoding endothelin converting enzyme 1, is a positional candidate gene for this locus, and was less expressed in HcB-8 bone. We hypothesized that the same genetic factors would impose analogous developmental tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Previous work in our laboratory using the recombinant congenic mice HcB-8 and HcB-23 identified ECE-1, the gene encoding ECE-1, as a positional candidate for a pleiotropic quantitative trait locus influencing bone strength and size in skeletally mature mice (Saless et al 2009(Saless et al , 2010(Saless et al , 2011aKristianto et al 2016). In these mice, higher expression of ECE-1 is associated with the presence of larger, stronger, and denser bones (Wang et al 2013). We hypothesized that big ET-1 signaling promotes osteoblast differentiation and mineralization in normal physiology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work in our laboratory using the recombinant congenic mice HcB-8 and HcB-23 identified ECE-1, the gene encoding ECE-1, as a positional candidate for a pleiotropic quantitative trait locus influencing bone strength and size in skeletally mature mice (Saless et al 2009(Saless et al , 2010(Saless et al , 2011aKristianto et al 2016). In these mice, higher expression of ECE-1 is associated with the presence of larger, stronger, and denser bones (Wang et al 2013). We hypothesized that big ET-1 signaling promotes osteoblast differentiation and mineralization in normal physiology.…”
Section: Introductionmentioning
confidence: 99%
“…In these mice, higher expression of ECE‐1 is associated with the presence of larger, stronger, and denser bones (Wang et al. ). We hypothesized that big ET‐1 signaling promotes osteoblast differentiation and mineralization in normal physiology.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cells are the primary source of ET1 and have a high density of EDNRB, so autocrine signaling favors vasodilation and hypotensive responses, while paracrine signaling leads to hypertensive responses. In experiments we performed using the same mice in which we identified Ece1 as a candidate gene for bone biomechanical performance, we found that mice harboring a high-expressing Ece1 allele had larger femoral and arterial cross-sections, greater arterial compliance, and lower BP than mice harboring a low-expressing Ece1 allele 52 .…”
Section: Future Considerationsmentioning
confidence: 89%
“…The LCCA was stretched 150% axially to mimic in vivo length (Tian et al, 2013; Wang et al, 2013a), pressurized to 90 mmHg, and allowed to equilibrate at 37°C for 30 minutes. Sinusoidal pressure cycles of 90-120 mmHg at 1 Hz were applied for pre-conditioning to achieve a consistent mechanical response (Fung et al, 1979).…”
Section: Methodsmentioning
confidence: 99%